Digital marketing communication of skincare products to develop men's consumptive behaviour - Putranto, Teguh Dwi; Suyanto, Bagong; Ariadi, Septi (Faculty of Communications Science, Dr. Soetomo University, 2022)
Having an attractive appearance is now not only for women but also for men. Taking care of the body, especially the face has become a new culture that has shifted the masculine side towards metrosexuals. To get an attractive appearance, a series of treatments are needed, one of which is skincare which requires much money. Such self-care behaviour, of course, also encourages men's consumerism. This study determines how digital marketing communication for skincare products builds men's consumptive behaviour on Instagram. Content analysis of Instagram posts related to the consumption of skincare products collected through the hashtag #scarlettlakilaki was used in this study. The results obtained that the element of dependence is 0.94 or 94 per cent. Then the result is considered credible because it exceeds the minimum threshold. This research concludes that Scarlett transforms masculinity into metrosexuality, blur a gender bias, and builds on the idea that the body of men who use Scarlett is depicted with a pure white body resembling a women's body.